2023
DOI: 10.1177/10600280231205023
|View full text |Cite
|
Sign up to set email alerts
|

Naloxegol versus Methylnaltrexone for Opioid-Induced Constipation in Critically Ill Patients

Daniel Tobben,
Sheniece Carpenter,
Rachel Kolar
et al.

Abstract: Background: Constipation impacts 58% to 83% of critically ill patients and is associated with increased time on mechanical ventilation, delirium, and increased length of stay (LOS) in the intensive care unit (ICU). Objective: The purpose of this study was to evaluate the efficacy of enteral naloxegol (NGL) versus subcutaneous methylnaltrexone (MNTX) for the management of opioid-induced constipation (OIC) in critically ill patients. Methods: A retrospective analysis was conducted on adult patients admitted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…While conducting studies on symptom management in cancer patients seems difficult and fraught with recruitment challenges, head-to-head comparisons of laxatives versus PAMORAs or different PAMORASs against each other are even rarer, even in patients with non-cancer pain who are easier to recruit. We only found one retrospective study comparing oral naloxegol with subcutaneous methylnaltrexone [ 48 ]; however, this study was conducted in seriously ill patients in an intensive care unit setting and included only 30 cancer patients (15% of patients in the naloxegol group and 28% in the naltrexone group had cancer). They found that both drugs increased SBMs and that naloxegol was non-inferior to subcutaneous methylnaltrexone at a significantly reduced cost.…”
Section: Discussionmentioning
confidence: 99%
“…While conducting studies on symptom management in cancer patients seems difficult and fraught with recruitment challenges, head-to-head comparisons of laxatives versus PAMORAs or different PAMORASs against each other are even rarer, even in patients with non-cancer pain who are easier to recruit. We only found one retrospective study comparing oral naloxegol with subcutaneous methylnaltrexone [ 48 ]; however, this study was conducted in seriously ill patients in an intensive care unit setting and included only 30 cancer patients (15% of patients in the naloxegol group and 28% in the naltrexone group had cancer). They found that both drugs increased SBMs and that naloxegol was non-inferior to subcutaneous methylnaltrexone at a significantly reduced cost.…”
Section: Discussionmentioning
confidence: 99%